China’s three north shelter forest program: cost–benefit analysis and policy implications - Suo, Xinhao; Cao, Shixiong (Environment, development and sustainability, 2021)
Sandstorms and soil erosion are serious problems around the world, but particularly in arid northern China. In response to these problems, the Chinese government has implemented the world's largest shelter forest construction project: the Three North Shelter Forest Program (TNSFP). However, we do not know how successful the program has been, because no one has carried out a comprehensive cost–benefit analysis. To analyze the benefits of the different ecological restoration methods implemented under the TNSFP and provide guidance for future ecological restoration efforts, we developed an improved cost–benefit analysis method that considers as many of the benefits and costs (including opportunity costs) as possible, subject to data availability, thereby clarifying the net benefit after accounting for these costs. We found different net benefits for the restoration types implemented under the TNSFP. The lowest net benefit was for afforestation by planting, at − 6.8 × 10 3 RMB ha −1 year −1 , which was negative due to its high costs; in contrast, the highest net benefit was for fruit tree plantations, at 53.3 × 10 3 RMB ha −1 year −1 , and this resulted from its high product value. There were large differences among regions in China, which indicates that the regional governments should adjust the balance among the ecological restoration measures in their region to account for the unique local conditions and maximize the net benefits of ecological restoration.